(untitled) - Jaramillo, Santiago (Hoboken, New Jersey, 2017)
Many organizations fail to realize and harness the power of their most valuable asset—their employees. Though they can be developed into a true competitive advantage, engagement isn't attainable if the employee isn't invested in the company's overall success. Agile Engagement offers business leaders a concrete strategy for building, maintaining, and utilizing employee engagement to achieve the highest level of business success. The key? Employees must feel like they are a part of their company's culture instead of having it handed down to them. Stories of failed employee engagement initiatives abound, and they all have one thing in common: they begin from the premise of "initiative" rather than "employee." True engagement occurs when an employee's heart and mind are activated in a way that leads to their motivation and commitment to positively impact the company's goals and vision.
Keywords: Hành vi tổ chức,Organizational behavior